Assessment of metal contamination in sediments in the tributaries of the Euphrates River, using pollution indices and the determination of the pollution source, Turkey - Kalender, Leyla; Ucar, Suna Cicek (Elsevier Science Bv, 2013)
The study area is located between 428120N latitude and 510760E longitude. The collected samples were vertical (sandbar) and stream sediments along the Geli Stream bed. Total concentrations of metals in the sediments were determined to evaluate the level of contamination. The median concentrations of As, Cu, Pb, Zn, Ag, Ni, Co, Mn, Cd, Sb, Cr, Ti and Al exceeded the concentrations in normal/background granodioritic rocks. Sediment pollution assessment was carried out using contamination factor (CF), pollution load index (PLI), enrichment factor (EF) and geoaccumulation index (Igeo). The metal concentrations in the assessed sediment samples (Geli Stream and sandbar) were compared with consensus-based TEC and PEC values. The CF values for As, Cu, Ni, Co and Cr >10 in sediments in the Geli Stream denote very high contamination by these metals. The PLI value indicated that the Geli Stream was moderately polluted. The highest Igeo values of Sb and Cr were found to be extremely polluted in sediments. The highest EF values of Sb, As and Cr were above 50, indicating extremely severe enrichment. Ecotoxicological indices (SQG) were used to assess the contamination levels of surface sediments. In this study, As and Cu in stream sediments were determined to be heavily polluted (37.95 ppm and 85.12 ppm; and Cr moderately polluted (64.50 ppm). Moreover, heavy metal concentrations were assessed from the sediment samples and were compared with consensus-based PEL, TEL, LEL, MET, ERL, PEC and TEC values. In the Geli Stream sediments, As, Ba, Cr, Cu, Pb, Ni and Zn were higher than all these consensus-based values. In the sandbar, As and Cu values were higher than TEL, LEL, MET and TEC values, and Ba values were higher than PEC and TEC values. Anomaly maps were drawn on the drainage networks according to pollutant elements. This indicated that the possible source of pollution was located northeast of the study area. Pollution contributed to the geochemical prospection studies and was determined as a possible mineralization setting. Element distribution in the direction of the stream flow path was assessed by factor analysis. The factor analysis indicated that source of metals are derived from both lithologic units and mineralizations. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Sediment pollution indices; Geochemical prospecting; East Euphrates